"This is not a parable": Transformations of the Prodigal Son in Turgenev, Dostoevsky, and Coetzee - Bolin, John (Studies in the novel, 2018)
Since Watt, the novel's eventual cultural predominance has often been read as inseparable from the ascendance of secularism and the demise of religious thought. The novel's master-plot has thus naturally been understood as a historical one not unlike Lukács's account of an individual becoming within a temporality without transcendence. yet it is interesting that neither secular history nor what Girard called 'transcendent presence that is free to abrogate becoming' can account for the way some major novels generate multiple, fiercely oppositional meanings through a complex play with literary mode and narrative models of temporality. This essay reads some revisions of parable in modern Russian literature, and then Coetzee's co-opting of that tradition in The Master of Petersburg, to consider how such fictions can complicate any boundary between the secular and the religious minds as they dramatize the search for a master-plot itself as a problem for the novel.